2021
DOI: 10.1016/j.jcot.2021.03.021
|View full text |Cite
|
Sign up to set email alerts
|

Tendon transfers for irreparable rotator cuff tears

Abstract: Symptomatic irreparable rotator cuff tears pose a challenge for shoulder surgeons. Whilst reverse polarity shoulder arthroplasty is an effective option for older symptomatic patients who have exhausted conservative management, the optimal treatment for younger patients remains controversial. In this article we outline the main tendon transfer options, including anatomical considerations, indications, contraindications, surgical technique, complications and a review of the evidence. Tendon transfers provide an … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
12
0
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(13 citation statements)
references
References 81 publications
0
12
0
1
Order By: Relevance
“…Latissimus dorsi and trapezius tendon transfers show encouraging results in specific patient groups. Recent reviews report large increases in shoulder scores across several series [ 16 , 101 , 102 ]; improved shoulder function may persist over 10 years[ 103 ]. A comparative study by Cavalier demonstrated an inferior Constant score at 12 months with latissimus dorsi tendon transfer compared to PCR and RSA, and a randomised trial of 42 patients reported inferior functional scores for LDTT compared to SCR [ 16 , 68 ].…”
Section: Discussionmentioning
confidence: 99%
“…Latissimus dorsi and trapezius tendon transfers show encouraging results in specific patient groups. Recent reviews report large increases in shoulder scores across several series [ 16 , 101 , 102 ]; improved shoulder function may persist over 10 years[ 103 ]. A comparative study by Cavalier demonstrated an inferior Constant score at 12 months with latissimus dorsi tendon transfer compared to PCR and RSA, and a randomised trial of 42 patients reported inferior functional scores for LDTT compared to SCR [ 16 , 68 ].…”
Section: Discussionmentioning
confidence: 99%
“…In order to achieve good results when considering tendon transfer reconstruction, certain important principles must be taken into consideration: a good understanding of anatomical relationships of the neurovascular bundles is vital for safe and effective transfers preserving muscle function, the transferred muscle must be elongated without compromising the donor site, the excursion and tension of the two muscles should be similar as the line of pull of both muscles, and the transferred muscle should acquire one of the functions of the recipient muscle ( 35 ). On the other hand, the tissue bed where the transferred tendon is supposed to glide must be free of oedema or scarring tissue, the tendon should function on a mobile and stable joint, the reimplantation site must be accurate with strong primary stability, and the surgeon must take care to use a meticulous technique in order to avoid unnecessary scarring of the tissue that will prevent tendon gliding ( 36 , 37 , 38 ).…”
Section: Tendon Transfers For Massive Cuff Tearsmentioning
confidence: 99%
“…Contra indications for tendon transfer are infection, a stiff joint, glenohumeral advanced arthritis, axillary nerve palsy, brachial plexus palsy or dysfunction affecting the muscle to be transferred, a posterosuperior tear massive tear associated with a non-reparable SST tear, and an anterosuperior massive tear associated with a non-repairable infraspinatus ( 36 ).…”
Section: Tendon Transfers For Massive Cuff Tearsmentioning
confidence: 99%
See 1 more Smart Citation
“…13 Such "disruptive" technologies seek to lower the surgical risks and morbidities associated with tendon transfers which require a more extensive surgical dissection. 14 Ever-increasing management options for the challenging cuff notably include Reverse Shoulder Arthroplasty (RSA). Although it was designed and advocated for use in Cuff Tear Arthropathy, the reliability of outcomes from this technique has seen its indications extend to patients with rotator cuff tears, with no arthritis.…”
Section: Contents Lists Available At Sciencedirectmentioning
confidence: 99%